Evaluation of controlled-release compound fertilizers in soil - Hanafi, M. M.; Eltaib, S. M.; Ahmad, M. B.; Syed Omar, S. R. (Taylor and Francis Group, 2002)
Evaluation of compound controlled-release fertilizer (CRF) in the soil is essential in order to establish an appropriate soil management and fertilizer application technique. A compound fertilizer containing about 15% nitrogen (N), 2% phosphorus (P), 16% potassium (K), 4% calcium (Ca), 1% magnesium (Mg), and 1% copper (Cu) was prepared and subsequently coated with natural rubber (NR), polyvinyl chloride (PVC), polyacrylamide (PA), and polylactic acid (PLA). Evaluations of the compound CRF were conducted in the laboratory and in the field using an open leaching technique. The soil column was prepared using an acid Bungor soil (Typic Paleudult) packed in PVC tube for the laboratory and an undisturbed soil column for the field studies. A 25-g sample of each coated fertilizer was mixed with the soil in the top (0-60 mm) of the soil column. Nutrients released by the compound CRF in the appropriate soil column were monitored in the leachate for 30 d (about 18.0 pore volume (PV) of leachate), while in the field they were exposed to the atmosphere for about 90 d. The uncoated compound fertilizer gave significantly (P ≤ 0.05) higher amount of nutrient loss compared to the coated fertilizers during leaching in the laboratory. The values ranged from 3023.0 mg N (80.3% of that added) to 1.4 mg Cu (6.2% of that added). Among the coated fertilizers, there were wide variations in the amounts and types of nutrient losses between different coating materials. By taking the summation of nutrients in the leachate, the effectiveness of the uncoated and coated compound fertilizers decreased in the order: PVC ≈NR < PLA > PA ⋙ uncoated. Depth distribution of nutrients and their amounts remaining in the soil column of the respective treatments showed no significant difference between leaching in the laboratory and that in the field. Thus, the effectiveness of the compound uncoated and coated fertilizers was similar to that measured in the laboratory using a fraction collector. Therefore, an assessment of the CRF could be done precisely and accurately in the laboratory using an open leaching technique. However, the effectiveness of CRF needs to be validated in the presence of a growing plant.